PENGARUH HUBUNGAN ANTARA DISIPLIN BELAJAR DAN PRESTASI BELAJAR SISWA SD NEGERI DI DESA KALIWUNGU, KECAMATAN KALIWUNGU PADA SEMESTER I TAHUN PELAJARAN 2022/2023 - Greget Widhiati; Suwardi Suwardi (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
Discipline is defined as an effort to control oneself and the mental attitude of the individual or society in developing obedience and obedience to the rules and regulations based on encouragement and awareness that arises from the heart. If it is associated with learning, the discipline of learning is more related to the mental attitude of the individual in his obedience to carrying out learning activities The research was conducted at SD Negeri Kaliwungu 01 and SD Negeri 02 in Kaliwungu Village, Kaliwungu District. The research sample was taken by purposive sampling. The variable of this research is learning discipline as the independent variable, which is measured by two sub-variables, namely learning discipline in the school environment and family environment. The second variable is learning achievement as the dependent variable. The results showed that there was a relationship between the sub-variables of learning discipline in the school environment and learning achievement, but its contribution was very weak. This can be seen from the value of the correlation coefficient is 0.064 with a significance value on both sides of 0.491>0.05. While the sub-variable of learning discipline in the family environment also has a relationship with learning achievement with the value of the correlation coefficient is 0.183 with a significance value on both sides of 0.043 <0.05. In addition, the two sub-variables are interrelated which shows the correlation coefficient value of 0.366 with a 2-sided significance = 0.000 <0.05. Overall, the results of this study also show that there is a relationship between learning discipline variables (both school and family environments) with student achievement at SDN Kaliwungu 01 and 02. This relationship is known by the Kendall concordance test with a correlation coefficient of 0.539 and Asymp. Sig. =0.000<0.05. These results indicate that there is a relationship between learning discipline and learning achievement. In addition, the magnitude of the effect on achievement is 53.9%.